2018
DOI: 10.1002/1873-3468.13216
|View full text |Cite
|
Sign up to set email alerts
|

Redox‐control of chlorophyll biosynthesis mainly depends on thioredoxins

Abstract: In order to maintain enzyme stability and activity, chloroplasts use two systems of thiol-disulfide reductases for the control of redox-dependent properties of proteins. Previous studies have revealed that plastid-localized thioredoxins (TRX) and the NADPH-dependent thioredoxin reductase C (NTRC) are important for the reduction of cysteine residues of enzymes involved in chlorophyll synthesis. Very recently, it was shown that the pale green phenotype of the ntrc mutant is suppressed when the contents of 2-cyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…The analysis of the redox state of Trxs f , FBPase and PRK in the suppressed line fully confirmed this hypothesis hence uncovering the central function of 2-Cys Prxs in chloroplast redox regulation (Pérez-Ruiz et al, 2017). Moreover, the suppressed line also recovered wild type levels of chlorophyll biosynthesis enzymes (Richter et al, 2018), indicating that the suppressor effect caused by decreased levels of 2-Cys Prxs is exerted beyond the enzymes of the CBC. Based on these results, we proposed a model according to which the redox balance of 2-Cys Prxs, which is maintained by NTRC and NADPH, modulates the light-dependent reduction of redox regulated enzymes based on Fdx reduced by the photosynthetic electron transport chain, which is fueled to stromal Trxs via the action of FTR (Pérez-Ruiz et al, 2017).…”
Section: The Central Role Of 2-cys Prxs: Integrating Antioxidant and mentioning
confidence: 97%
“…The analysis of the redox state of Trxs f , FBPase and PRK in the suppressed line fully confirmed this hypothesis hence uncovering the central function of 2-Cys Prxs in chloroplast redox regulation (Pérez-Ruiz et al, 2017). Moreover, the suppressed line also recovered wild type levels of chlorophyll biosynthesis enzymes (Richter et al, 2018), indicating that the suppressor effect caused by decreased levels of 2-Cys Prxs is exerted beyond the enzymes of the CBC. Based on these results, we proposed a model according to which the redox balance of 2-Cys Prxs, which is maintained by NTRC and NADPH, modulates the light-dependent reduction of redox regulated enzymes based on Fdx reduced by the photosynthetic electron transport chain, which is fueled to stromal Trxs via the action of FTR (Pérez-Ruiz et al, 2017).…”
Section: The Central Role Of 2-cys Prxs: Integrating Antioxidant and mentioning
confidence: 97%
“…It has been shown that a deficiency of f- and m-type TRX variants and NTRC leads to an obvious pale-green leaf phenotype and multiple defects in the TBS pathway [ 10 , 11 ]. Thus far, four TBS enzymes have been proved to be targets of TRX and NTRC for the reduction of thiol bonds: the rate-limiting enzyme glutamyl-tRNA reductase (GluTR) [ 10 , 12 ], magnesium protoporphyrin IX methyltransferase (CHLM) [ 10 , 12 , 13 , 14 ], the I subunit of magnesium chelatase (CHLI) [ 11 , 15 ] and the Mg–protoporphyrin monomethylester cyclase (CHL27) [ 16 ]. Among other TBS enzymes, glutamate 1-semialdehyde aminotransferase (GSAAT), 5-aminolevulinic acid dehydratase (ALAD), protoporphyrinogen oxidase (PPOX) and protochlorophyllide oxidoreductase (POR) were suggested to be the potential interacting partner of TRXs and NTRC [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Major biological functions of plant thioredoxins include posttranslational redox regulation of a wide array of proteins, participation in antioxidative scavenging and signaling networks, overcoming oxidative damages to macromolecules as well as intercellular communication [ 6 , 25 , 26 ]. Several isoforms of thioredoxins ( f -, m -, x -, y -, and z -type) have been identified in chloroplasts, and their main biological role is associated with modulation of activity of target proteins involved in photosynthesis process [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to these authors, the two thioredoxin systems present in chloroplasts work together in order to regulate the plant growth under diverse light conditions. Richter et al [ 6 ] claimed that redox-control biogenesis of chlorophylls in higher plants is mainly linked to functioning of a wide spectrum of thioredoxins. In addition, A. thaliana seedlings with inactivated expression of three m -type thioredoxins-encoding genes (i.e., Trxm1 , Trxm2 , Trxm3 ) had a lower content of chlorophylls and their metabolites in relation to the wild-type plants [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation